Affect in language learning (Cambridge university press, 1999)
The affective domain and the emotional factors that influence language learning have been of interest in the field of language teaching for a number of years. By proposing a holistic approach to the learning process, this volume takes the position that the language learning experience will be much more effective when both affect and cognition are considered. The eighteen chapters discuss issues such as memory, anxiety, self-esteem, facilitation, autonomy, classroom activities, and assessment from the perspective of affect.